IMPLEMENTASI MANAJEMEN STRATEGIK DALAM PENYUSUNAN RENCANA KERJA SMP TUNAS MEKAR INDONESIA BANDAR LAMPUNG - A. Daiyuni Kartika Sari; Riswanti Rini; Supomo Kandar (9 772338317006)
The aim of the research was to describe the implementation of Strategic Management in Arranging the School Plan in SMP Tunas Mekar Indonesia Bandar Lampung. This qualitative research applied data collection techniques through observation, documentation and interviews. The data sources were the leaders of Sekolah Tunas Mekar Indonesia, School Committee (Parents Association), and teacher. The results of the research were SMP Tunas Mekar Indonesia: 1) has formed a School Development Team as the first step of strategic management process, 2) has formulated school vision, mission and goal as the prime basic of school programs, 3) The process of Arrangement of School Plan was through 5 steps, 4) The Implementation of School Plan had been through some steps which were: monitoring, evaluating, reporting, renewing. Tujuan penelitian untuk menjelaskan implementasi manajemen strategik dalam penyusunan rencana kerja sekolah di SMP Tunas Mekar Indonesia Bandarlampung. Penelitian kualitatif ini mengaplikasikan teknik pengumpulan data melalui observasi, dokumentasi, dan wawancara. Sumber data adalah kepala sekolah, wakil kepala sekolah, guru, Komite Sekolah, dan ketua yayasan. Hasil penelitian: 1) Sekolah membentuk Tim Pengembang Sekolah sebagai tahap perencanaan dari manajemen strategik, 2) Perumusan visi, misi dan tujuan sekolah sebagai landasan untuk program sekolah, 3) Proses penyusunan Rencana Kerja Sekolah dan Rencana Kerja Tahunan melalui 5 tahap, 4) Implementasi RKS mealui tahap pelaksanaan, monitoring, evaluasi, pelaporan dan pembaharuan. Kata kunci: implementasi, manajemen strategik, rencana kerja sekolah